Penerapan Kolaborasi Triple Helix untuk Pengembangan Kapasistas Pemasaran Desa Wisata Melalui Platform Digital - Taufiqqurrachman Taufiqqurrachman; Ringgo Eldapi Yozani; Mashur Fadhli; Fahmi Muhammad; Riau Nurita (Unri Conference Series: Community Engagement, 2025)
Digital platforms have become a fundamental instrument in tourism marketing, especially for developing and promoting tourism villages. However, many village management units still face significant limitations in human resources and digital skills. This community service program was designed to address these challenges in Tourism Village of Sungai Petai through the application of a triple helix collaboration model, which synergizes the roles of academics, local government, and tourism business actors. Within this framework, academics contributed expertise and mentorship, the village government provided policy and logistical support, while local businesses shared practical knowledge relevant to digital promotion and entrepreneurship. The program employed a problem-based learning approach, encouraging participants to identify real issues, formulate strategies, and produce digital content that reflects the village’s cultural and environmental uniqueness. Training materials covered the principles of integrated tourism marketing—encompassing destination image, halal tourism, and sustainability—as well as techniques for visual content creation and social media management. The evaluation design incorporated both pre-test and post-test assessments to measure the participants’ knowledge gains. The findings indicate a measurable improvement, with the average pre-test score of 51.3 increasing to 80.3 after the training, reflecting a 56.6% growth in participants’ digital marketing competence. This significant increase demonstrates that the triple helix model effectively enhances local capacity in managing digital promotion and strengthens the foundation for sustainable village tourism development. In conclusion, the program not only improved participants’ technical understanding of digital marketing but also fostered a collaborative mindset essential for sustaining innovation at the community level. The outcomes affirm that the triple helix approach can serve as a replicable model for empowering rural communities toward inclusive and sustainable digital tourism transformation.